2021
DOI: 10.2147/rmhp.s297564
|View full text |Cite
|
Sign up to set email alerts
|

Pooled Prevalence and Determinants of Prelacteal Feeding Practice in Eastern Africa Evidence from Demographic and Health Survey Data: A Multilevel Study

Abstract: Background: Despite the benefits of breast milk and colostrum for the health and survival of children, early prelacteal feeding is commonly practiced worldwide, particularly in lowand middle-income countries. The aim of this study was to evaluate the pooled prevalence and determinants of prelacteal feeding in Eastern Africa. Methods: This study was carried out within 11 East African countries from 2010 to 2018, a pooled study of prelacteal feeding was performed. For assessing model fitness and contrast, intra-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
2
11
2
1
Order By: Relevance
“…This study evidenced that the odds of prelacteal feeding practice were higher among mothers who had multiple births as compared to mothers who had single births. This finding is similar to studies conducted in different parts of Ethiopia [ 13 , 14 , 21 , 17 ]. This could be due to the probability of giving preterm birth was higher among women who gave multiple births than those who gave single births [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study evidenced that the odds of prelacteal feeding practice were higher among mothers who had multiple births as compared to mothers who had single births. This finding is similar to studies conducted in different parts of Ethiopia [ 13 , 14 , 21 , 17 ]. This could be due to the probability of giving preterm birth was higher among women who gave multiple births than those who gave single births [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…Different studies conducted in the country showed that lack of breastfeeding counseling, avoidance of colostrum, birth spacing, Antenatal care (ANC) visit, wealth index, mode of delivery, initiation of breastfeeding, place of delivery, type of residence, and type of birth are factors that affect prelacteal feeding practice [ 8 , 12 , 13 , 16 , 17 ]. In Ethiopia, the prevalence of prelacteal feeding practice was ranged 10.1%-56% [ 7 , 9 , 12 , 13 , 14 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A multi-level analysis of data from 22 countries in sub-Saharan Africa for risk factors of prelacteal feeding found a 32.2% prevalence of prelacteal feeding, with the likelihood being higher among mothers with a low level of education, preceding birth intervals of less than 24 months, low antenatal care attendance, home delivery, and small-sized baby at birth [ 1 ]. In East Africa, the pooled prevalence of prelacteal feeding is 12% [ 2 ]. One systematic review and meta-analysis conducted in Ethiopia reports a 25.3% pooled prevalence for prelacteal feeding, with the likelihood being lower among mothers that attended antenatal care during the most recent pregnancy, received counseling on infant feeding practices, timely initiated breastfeeding, and resided in an urban setting.…”
Section: Introductionmentioning
confidence: 99%
“…This practice increases the risk of illness among newborns and prevents them from the protective effects and vital nutrients in the colostrum (6). Regardless of its detrimental effects on health, prelacteal feeding is frequently practiced worldwide, particularly in developing countries, including Indonesia (6,7). One of the most crucial feeding practices recommended by The World Health Organization (WHO) in the Global Strategy for Infant and Young Child Feeding is exclusive breastfeeding, defined as the practice of only giving infant breastmilk for the first 6 months of life (8).…”
Section: Introductionmentioning
confidence: 99%
“…This practice increases the risk of illness among newborns and prevents them from the protective effects and vital nutrients in the colostrum ( 6 ). Regardless of its detrimental effects on health, prelacteal feeding is frequently practiced worldwide, particularly in developing countries, including Indonesia ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%